Information sharing in construction supply chain management performance: A preliminary study - Mohtar, Shamimi; Mohamed Udin, Zulkifli; Zulhumadi, Faisal (2010)
In the present competitive industrial and business environment, information becomes one of the most valuable assets to organisations, since information is anything that reduces uncertainty. The utilisation of information that flows within the organisation is an important process. Information that flows from one entity or functional area to another should be able to support the management in formulating strategy. Focusing on the information supply chain in isolation is a shortcoming, as most managers realise that information is needed from the whole supply chain in order to make a sound decision. Supply Chain Management (SCM) has been adopted in various industrial contexts, namely manufacturing, textiles, healthcare, and foods. In this paper, the focus is on the construction supply chain, which in Malaysia has been emphasised upon by the Malaysian government through the Construction Industry Development Board (CIDB) to accelerate its practices among the industry players. The important aspect to realise the implementation of SCM is regarding information sharing practices. This paper presents an overview of information flow in the organisation, information supply chain, and construction supply chain, in order to understand the basis to information sharing practices. A brief explanation is given on the methodology used in the research, and the paper concludes with some insight regarding information sharing practices in the construction supply chain.